2009
DOI: 10.1177/0193945909343293
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stress Resiliency on RN Job Satisfaction and Intent to Stay

Abstract: Registered nurse (RN) job satisfaction is a major predictor of intent to stay and job turnover, serious concerns to health care leaders. Predictors of job satisfaction include autonomy, control over daily practice, nurse-physician collaboration, transformational leadership, group cohesion, job stress, structural empowerment, and psychological empowerment. In the model of psychological empowerment, stress resiliency is the product of persons' interpretive styles and influences psychological empowerment. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 48 publications
6
82
1
11
Order By: Relevance
“…Although a number of articles identified in this review have confirmed significant relationships between work related stressors and burnout [25,26,27,28,29,30,31,32,33,34,59,60,77,78], job satisfaction [11,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,58,59,60,61,62,63,64,65,66,81] as well as general health, these relationships are predominantly two way relationships with only a handful of studies confirming three way relationships [64,65,71,84]. Among the studies confirming two way relationships, only one study confirming the relationship between job satisfaction and general health [85] was identified.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although a number of articles identified in this review have confirmed significant relationships between work related stressors and burnout [25,26,27,28,29,30,31,32,33,34,59,60,77,78], job satisfaction [11,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,58,59,60,61,62,63,64,65,66,81] as well as general health, these relationships are predominantly two way relationships with only a handful of studies confirming three way relationships [64,65,71,84]. Among the studies confirming two way relationships, only one study confirming the relationship between job satisfaction and general health [85] was identified.…”
Section: Discussionmentioning
confidence: 91%
“…It has also been found that the interaction between workload and autonomy best predicts job satisfaction [44]. A common conclusion was that work related stress is significantly related to job satisfaction [49,50] and nurses who experience higher stress levels are less satisfied with their jobs [51]. Further details about the method, sample and findings of identified articles are included in Table 2 below.…”
Section: Resultsmentioning
confidence: 99%
“…Another difference between this study and other studies 26 - 27 is that the nurses here did not experience fatigue from the exposure to problems, even though they showed some degree of wanting to leave the bedside. The results of the investigation 28 showed that empowerment is a predictor of job satisfaction and a factor supporting the retention of employees in the workplace and in determining whether they will avoid leaving the profession. …”
Section: Discussionmentioning
confidence: 99%
“…Microlevel theories relevant to leadership and management functions in PH and macrolevel organizational theories related to structure or effectiveness were examined. Recent studies emerged that are recognizing the importance of a phenomenon called ''empowerment'' to reach satisfaction on the job (Almost & Laschinger, 2002;Armstrong & Laschinger, 2006;Cho, Laschinger, & Wong, 2006;Larrabee et al, 2010;Laschinger & Finegan, 2005;Laschinger, Finegan, Shamian, & Wilk, 2004;Manojlovich & Laschinger, 2002). The author concluded that it is plausible to study the stability factors (job retention) of nurses in community/PH by measuring their job satisfaction and linking their appreciation for organizational workplace attributes.…”
Section: Frameworkmentioning
confidence: 99%